Fatty Acid Composition of Rice Oils - Resurreccion, Adoracion P.; Juliano, Bienvenido O. (Wiley, 1975)
Analysis of rice oil methyl esters of two varieties by gas‐liquid chromatography showed that oil from bran‐polish and oil from milled rice extracted with petroleum ether had similar fatty acid composition and had oleic/linoleic acid ratios of about 1.0. However, milled rice oil extracted with chloroform/methanol had a higher linoleic acid content and a lower oleic acid content than oil extracted with petroleum ether.